2018
DOI: 10.1155/2018/8924703
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Noncavity-Distorting Intramural Fibroids on the Efficacy of In Vitro Fertilization-Embryo Transfer: An Updated Meta-Analysis

Abstract: Aim To address the impact of noncavity-distorting intramural fibroids on the efficacy of in vitro fertilization-embryo transfer (IVF-ET) outcomes. Methods The PubMed, Web of Science, Embase, Cochrane Library, and China National Knowledge Infrastructure were searched systematically. A meta-analysis was performed based on comparative or cohort studies that explored the impact of noncavity-distorting intramural fibroids on the efficacy of IVF-ET treatment. The IVE-ET outcomes of study group (women with noncavity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
(48 reference statements)
1
22
0
1
Order By: Relevance
“…26 Some women of advanced age who, in the past, underwent ART with their own oocytes are now able to undergo a heterologous fertilization with oocytes of younger donors. Wang et al 23 recently affirmed that no cavitydistorting intramural fibroids would significantly reduce implantation rate, clinical pregnancy rate, and live birth rate and significantly increase the miscarriage rate after IVF treatment, but it would not significantly increase the ectopic pregnancy rate. Kameda et al 24 reported on pregnancy rates in patients with infertility of unknown etiology other than the presence of uterine fibroids, concluding that laparoscopic myomectomy should be recommended in patients with fibroids and no obvious cause for infertility.…”
Section: Discussionmentioning
confidence: 99%
“…26 Some women of advanced age who, in the past, underwent ART with their own oocytes are now able to undergo a heterologous fertilization with oocytes of younger donors. Wang et al 23 recently affirmed that no cavitydistorting intramural fibroids would significantly reduce implantation rate, clinical pregnancy rate, and live birth rate and significantly increase the miscarriage rate after IVF treatment, but it would not significantly increase the ectopic pregnancy rate. Kameda et al 24 reported on pregnancy rates in patients with infertility of unknown etiology other than the presence of uterine fibroids, concluding that laparoscopic myomectomy should be recommended in patients with fibroids and no obvious cause for infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Any role of nonindenting fibroids in infertility remains to be determined, with some researchers finding no impact on fertility and others indicating a negative effect. [16][17][18][19][20][21][22][23] With regard specifically to pregnancy after ART, there have been several reports (including a metaanalysis) that showed a deleterious impact of fibroids upon assisted reproduction, including ICSI. 20,21,23 Thus, while speculative, it is possible that the resolution of the intramural fibroid after treatment with the Sonata System might have played a role in enabling successful ET postablation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of meta-analyses since 2007 reported different conclusions despite mostly including the same studies (2,3,4,5,6,7). This is likely to be the result of differences in the methodology of reviews and inclusion/exclusion criteria that were used.…”
Section: Introductionmentioning
confidence: 99%
“…We will look at six major reviews that analysed the impact of fibroids on reproductive outcomes (2,3,4,5,6,7). Three of these reviews included studies that investigated the impact of all-type fibroids on both spontaneous pregnancies and IVF treatment outcomes (2,3,4), and the other three specifically addressed studies that assessed the impact of intramural fibroids that did not distort the uterine cavity on the outcome of IVF treatment (5,6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation